Information and Communication Technologies to Improve Problem Solving and Self-Efficacy: Exploring Geometry Learning Using Dynamic Mathematics Software Geogebra - Mukhtar, Mukhtar; El Islami, R. Ahmad Zaky; Damanhuri, Damanhuri; Hamundu, Ferdinand Murni (Gemilang Maju Publikasi Ilmiah (GMPI), 2021)
Information and communication technologies can support learning of geometry through geogebra software. This study aimed to investigate the effectiveness of dynamic mathematics software geogebra towards problem solving and self-efficacy. Seventy-four university students divided to one class assigned as geogebra assisted learning and the other as using conventional learning. The results showed a significant difference of problem solving between these two groups statistically. Additionally, The results showed that there is a significant difference of self-efficacy between these two groups statistically. The results indicates that the problem solving and sef-efficacy of the university students using geogebra assisted better than using conventional learning. We can conclude that the dynamic mathematics software geogebra is effective to improve problem solving and self-efficacy